The effects of two different correction strategies on the snatch technique in weightlifting - Milanese, C.; Cavedon, V.; Corte, S.; Agostini, T. (Journal of Sports Sciences, 2017)
Improving motor skills represents one of the major issues in motor control and motor learning literature. The aim of this study was to investigate which of two strategies, method of amplification of error (MAE) or direct instruction (DI), would be more beneficial for error correction of the snatch technique. Thirty well-trained male weightlifters were randomly assigned to one of three training conditions (MAE, DI and Control). The experiment took place in only one practice session in which each lifter performed 3 pretraining trials, 8 training intervention trials, and 3 post-training trials, and a retention test session after 1 week. An optoelectronic motion capture system was used to measure the kinematic parameters of the weightlifting performance. After the training intervention, data showed that the MAE group revealed a greater improvement in several kinematic parameters when compared to the DI and Control groups, and the benefits derived from its application were still present 1 week later in the retention test. Nevertheless, the findings of the present study should be interpreted with caution due to the relatively small sample size; further research will also be necessary to evaluate the effects of MAE with different ability levels and other sport skills. The present findings could have practical implications for sport psychology and physical education because while practice is obviously necessary for improving learning, the efficacy of the learning process is essential in enhancing learners` motivation and sport enjoyment.